Case Report: A case of synchronous right upper lobe adenocarcinoma and left lower lobe squamous cell carcinoma treated with immune checkpoint inhibitor plus chemotherapy - Liu, Yujiao; Yu, Han; Dong, Youhong; Zhang, Dongdong (Frontiers in Oncology, 2023)
Globally, lung cancer is the leading cause of cancer-related mortality. Multiple primary lung cancers (MPLC) account for a very small portion of all primary lung cancer cases. Importantly, a quick and precise differentiation between MPLC and intrapulmonary metastases is directly related to patient prognoses as treatment strategies vary according to pathological type. Synchronous MPLC are most commonly seen in the same lung. Here, we report a rare case of a patient with synchronous MPLC of both lungs. A 67-year-old man, with a 1-month cough and expectoration history, was admitted in our hospital. Computed tomography (CT) chest scan revealed a lower lobe nodule in the left lung and an upper lobe nodule in the right lung. He underwent successive fiberoptic bronchoscopy and CT-guided percutaneous pulmonary aspiration biopsy of both lungs. The pathological diagnosis was squamous cell carcinoma of the left lung and adenocarcinoma of the right lung.